Gas chromatography – mass spectrometry analysis of acetone extract of Lactuca tatarica (L.) C. A. Mey. roots - Shukurlu, Emil Namik (Experimental Biology and Biotechnology, 2022)
Research work is devoted to the chemical investigation of the roots of the Lactuca tatarica (L.) C. A. Mey. by gas chromatography – mass spectrometry method. From the crude extract that is obtained from the roots, the presence of natural compounds of various groups has been detected. As a result, 25 different substances including acyclic compounds (methyl myristate, palmitic acid methyl ester, ethyl palmitate, methyl elaidate, methyl stearate, ethyl oleate, etc.) have been identified from the solid mass of the research object. The most abundant fatty acid esters are methyl oleate (6.831 %) and palmitic acid methyl ester (2.902 %). In addition, the triterpenoid compounds (lupeol acetate, cycloartenol acetate, 3β,13β,14β-13, 27-cycloursan-3-ol acetate) which are characteristic of the L. tatarica have been identified. Lupeol acetate is the predominant component which makes up 56.35 % of the whole obtained substances. Elaidic acid which belongs to the fatty acids group, bis(2-ethylhexyl)phthalate which belongs to the aromatic dicarboxylic acid esters and other compounds have also been identified. Among the identified substances, some are found previously from the other species of the genus Lactuca L. but with regards to the L. tatarica to the best of our knowledge the majority of them are firstly being reported in this study. The investigated plant is widespread in the lowlands and coastal areas of Azerbaijani flora. The availability of some pharmacological effective compounds (lupeol acetate, 3β,13β,14β-13, 27-cycloursan-3-ol acetate, olean-12-en-3-yl acetate) makes the research significant in terms of chemical aspect. Therefore, the results of this investigation open up new horizons for future studies in various fields including the pharmaceutical one.